UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING - Setiana, Beta; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
A manufacturing company is a company that has a very large production scale compared to other companies, so it can be compared with other company products as well. A company needs a plan to achieve company goals. The company's main goal is to increase it’s value. By increasing it’s value, investors can see that the condition of the company is good. The purpose of this study is to analyze and examine company size and leverage on firm value in manufacturing companies at food and beverage sub-sector through tax avoidance. Data analysis of hypothesis testing in this study uses Partial Least Square - Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis test using PLS 3.0 application show that company size has a positive but not significant effect on tax avoidance, leverage has a negative but not significant effect on tax avoidance, company size has a significant negative effect on firm value, leverage has a significant positive effect on firm value. Tax Avoidance has a positive but not significant effect on firm value. The results of indirect effect hypothesis test show that company size has a positive but not significant effect on firm value through tax avoidance, Leverage has a negative but not significant effect on firm value through tax avoidance,